5=(-2x)+3x

Simple and best practice solution for 5=(-2x)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=(-2x)+3x equation:


Simplifying
5 = (-2x) + 3x

Combine like terms: (-2x) + 3x = 1x
5 = 1x

Solving
5 = 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -1x = 1x + -1x

Combine like terms: 1x + -1x = 0
5 + -1x = 0

Add '-5' to each side of the equation.
5 + -5 + -1x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 0 + -5
-1x = 0 + -5

Combine like terms: 0 + -5 = -5
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

See similar equations:

| -3y=471 | | -32=3x+10 | | -106+2x=92-7x | | R^2+12=7R | | 12d=5*5 | | 28=4u-16 | | 11g-2g-12g=-39 | | d/10-1=-31 | | (4x+1)-(6x-5)= | | 9s=8*36 | | 136=-8(1+3a) | | 8n-(5n+4)=14 | | 19s+60=31-s | | 5[4(2m+n+3)-6m-1]+2(5m-n)= | | -8y-(x-4x)+3= | | 3x-150=-39 | | -7(k+3)-4k=-109 | | 3(x-8)=2(x+3) | | 5a-16-8a=-10 | | 4x+1.18=-3.1(2-.01x) | | 2g+3(-8+3G)=1-g | | (-10)=6+4x-6x | | 31-(2c+4)=2(c+6)+c | | 722=485+b | | (5s-2t)-(2s-4t)= | | 7a=36*21 | | X+59+84+X+51=180 | | 128=-8(-2+2p) | | 42p-39=66p-87 | | 7-3d-5=-1+2d-12+d | | 247=-7(-1+8b)-4b | | a+25=-8 |

Equations solver categories